Development and Content Validation of the Multifactoral Assessment of Perceived Social Support (MAPSS), a Brief, Patient-Reported Measure of Social Support for Use in HIV Care - Fredericksen, Rob J. (AIDS Care, 2019)
Low perceived social support negatively impacts health outcomes. HIV-related stigma may hinder social support. We developed a measure of perceived social support for use in HIV care. We developed a pool of legacy social support items based on literature review. We categorized items similar in content and winnowed items within each of these categories to the strongest alternatives using a qualitative item review process. We designed an interview guide representative of content areas, conducted concept elicitation interviews with patients in English/Spanish, and coded transcripts to match item pool content. We developed new items for salient unrepresented content. In focus groups, patients prioritized highly matched items. We performed cognitive interviews with patients on resulting high-priority items. We performed validity testing on final items against two legacy social support measures. From concept elicitation interviews (n=32), we matched the following concepts: sense of belonging/inclusion (e.g., feeling part of a community/group); communication (e.g., sharing thoughts/feelings with others, and vice-versa); emotional support (feeling loved/liked/cared about); feeling accepted by others as a person; companionship (e.g., fun with others); practical support (e.g., feeling that others in your life would offer tangible support). We identified a new concept: feeling supported by friends/family in remaining healthy. Focus groups (n=23) prioritized highly emotional support, communication, and support to remain healthy. Cognitive interviews (n=30) found most items were well-understood; we revised or omitted those that were not. The final 8-item measure performed well when administered to patients (n=708), with good construct validity. We used an Item Response Theory program to create a 3-item Short Form version of the measure, which captures 96% of patients indicating low social support. We developed the Multifactoral Assessment of Perceived Social Support (MAPSS) and Short Form (MAPSS-SF), which are brief, clinically relevant, sufficiently unidimensional measures of social support for use with patients living with HIV.